Health Priorities among Women Recently Released from Jail - Ramaswamy, Megha (Am J Health Behav, 2015)
OBJECTIVE: To describe the health priorities of women recently released from jail. METHOD: We open-coded semi-structured interview transcripts collected from 28 women within 6 months after their release from jail to identify themes associated with prioritization of health. RESULTS: Five out of 28 women listed health as their top post-release priority. However, many women had competing priorities after release, including housing, employment, and children. We found that women described several reasons why health was not a priority; however, participants reported regular use of the healthcare system upon release from jail, indicating that health was important to them to some degree. CONCLUSIONS: Our findings may inform intervention efforts that connect women to healthcare resources and increase health-promoting behavior during the transition from jail to community.